1993
DOI: 10.1007/bf00004600
|View full text |Cite
|
Sign up to set email alerts
|

Dietary carbohydrate utilization in cod (Gadus morhua): metabolic responses to feeding and fasting

Abstract: Moist diets with increasing amounts of carbohydrate (0.5%, 10% and 21% on a dry weight basis) were each fed to duplicate groups of cod (initial weight 370 g) for 8 weeks, after which all groups were fasted for 4 weeks. Protein energy was high and accounted for more than 70% of the gross energy content in all feeds, and the diets were maintained isocaloric by substituting lipid energy for carbohydrate energy. No indigestible binder was added. Excellent growth and feed conversion were obtained in all groups. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
34
1
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 34 publications
9
34
1
3
Order By: Relevance
“…The market value for cod liver is not as high as the market value for cod muscle, therefore it is desirable that cod use protein for muscle growth and reduce liver growth. Liver size can be reduced by starvation (Hemre et al, 1992;Jobling et al, 1994;Karlsen et al, 1994) and lower feeding frequencies (Dos Santos et al, 1993). To reduce feeding to near starvation will result in reduced muscle growth, which will not be economically for the farmer.…”
Section: Cod Gut Waste and Liver Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The market value for cod liver is not as high as the market value for cod muscle, therefore it is desirable that cod use protein for muscle growth and reduce liver growth. Liver size can be reduced by starvation (Hemre et al, 1992;Jobling et al, 1994;Karlsen et al, 1994) and lower feeding frequencies (Dos Santos et al, 1993). To reduce feeding to near starvation will result in reduced muscle growth, which will not be economically for the farmer.…”
Section: Cod Gut Waste and Liver Sizementioning
confidence: 99%
“…The same strategy will however not function for cod, as this species stores all surplus energy in the liver. Researchers have shown that a high fat content in cod feed gives enlarged liver Lie et al, 1988;Jobling et al, 1991;Hemre et al, 1992;Jobling et al, 1994;Morais et al, 2001;Rosenlund et al, 2004;Karlsen et al, 2006). Also increased dietary starch seems to increase fat and glycogen deposition in liver (Hemre et al, 1989).…”
Section: Cod Gut Waste and Liver Sizementioning
confidence: 99%
“…Les valeurs observées pour l'hématocrite, l'hémoglobine et le nombre de globules rouges sont comparables à celles présentées dans la bibliographie pour différentes espèces de poissons (ROMESTAND, 1983 ;PEREZ et al, 1989 ;HEMRE et al, 1990 ;PEARSON et STEVENS, 1991 ;VELLAS et al, 1994). Des modifications de ces paramètres ont été signalées lors d'un état de stress (SOIVIO et OIKARI, 1976 ;WITTERS et al, 1990 ;WELLS et WEBER, 1991 ;BARTON et IWAMA, 1991) mais de telles variations n'apparaissent pas clairement dans notre étude puisque nous n'avons pas constaté de relation significative avec la glycémie, considérée comme indicateur de stress (COMTE, 1995).…”
Section: Discussionunclassified
“…Nos résultats ne confirment qu'en partie ces observations car la diminution de l'hématocrite et du nombre de globules rouges est amorcée avant la fin de l'été. De nombreux auteurs ont constaté une diminution de ces descripteurs lorsque les poissons étaient à jeun ou dans un état nutritionnel défavorable (HICKEY, 1976 ;MAHAJAN et DHEER, 1983 ;PLUMB et al, 1986 ;HEMRE et al, 1990). Il est donc possible que les ressources naturelles du milieu ne suffisent pas à satisfaire les besoins des poissons, proportionnels à l'augmentation de la température.…”
Section: Discussionunclassified
“…Although carnivorous fish have limited capacity to use dietary carbohydrate (Hemre et al 1993, 1995a, Deng et al 2000, improved growth performance with high carbohydrate diets has been demonstrated in rainbow trout, Oncorhynchus mykiss (cf. Kim andKaushik 1992, Grisdale-Helland andHelland 1997), European eel, Anguilla anguilla (cf.…”
Section: Introductionmentioning
confidence: 99%